Den journalistiske dækning af toppolitikere på turne - Kristian Serge Skov-Larsen (Journalistica, 2006)
This article examines the effect of Mogens Lykketoft’s and Anders Fogh Rasmussen’s tours of the electoral campaign in 2005. The purpose of the tours was to use the local media in a more easy and unedited way to carry through the politics of the parties and at the same time to expose the two prime minister candidates. The conclusion of the article is that the behaviour of the local media does not correspond to the expectations, which the parties had prior to the tours. The media’s coverage of the tours is less than expected, more critical and with a less distinctive focus on politics than on process and persons. This means that the central party organisations ought to look for other ways to influence the local media – than by sending top politicians on tour.